Spot Toyota: Design and Development of a Mobile Application for Toyota’s Promotion Actions to the Young Audience - Nuno Martins; Joel Enes (Advances in Science, Technology and Engineering Systems Journal, 2020)
This project aims to demonstrate the importance that digital media can have to the development of loyalty programs, namely in creating empathy and proximity relationships between brands and their target audience: young people. This study consisted of the creation of a digital platform for Toyota Portugal, named Spot Toyota, to communicate actions promoted by the car brand, especially during music festivals. With the support of advertising agency Caetsu, this mobile application was developed to bring the brand closer to a younger audience – festival fans – with potential interest in two Toyota fleet car models: Aygo and C-HR. Through strategies typical of loyalty programs, such as the awarding of vouchers or coupons, the accumulation of points or winning prizes, a system was produced with the main focus on attracting users to the platform in a continuity perspective. The working process of this investigation resulted in the design of a smartphone application, based not only on the analysis of other examples present in the market but also on the understanding of crucial subjects such as loyalty programs, UX and UI design, application of personas models, creation of wireframes and workflows, and development of usability tests.
Keywords: Mobile App; UI & UX Design; Digital Design; Communication Design; Toyota